Задача с нелокальным условием на свободной границе - Тахиров, Ж.О.; Тураев, Р.Н. (Український математичний журнал, 2012)
Дослiджено однофазну задачу Флорiна з нелокальною умовою для параболiчного рiвняння. Доведено теореми єдиностi та iснування розв’язку, отримано апрiорнi оцiнки для розв’язку. We investigate the one-phase Florin problem for a parabolic equation with nonlocal condition. Theorems one the existence and uniqueness of a solution are proved, and a priori estimates for the solution are obtained.